Tactile graphical display for the visually impaired information technology applications - Shafik, M; Fekkai, S (Cranfield University Press, 2013)
This paper presents an interactive tactile graphical display, for the visually impaired information technology access applications. The display consists of a matrix of dots. Each dot is an electro rheological micro actuator. The actuator design and development process is presented in this paper. Prototype size 124x4 dots was manufactured. An advanced software tools and embedded system based on voltage matrix manipulation has been developed, to provide the display near real time control. The experimental tests carried out into the developed prototype showed that each actuator of the matrix was able to provide a vertical movement of 0.7 mm and vertical holding force of 100 to 200 mN. The stroke and dynamic response tests showed the practicability of the developed tactile display, for the visually impaired information technology applications.
Keywords: Visually Impaired IT applications; Tactile Graphical Display; ER- Industrial Applications